The human VGF-derived bioactive peptide TLQP-21 binds heat shock 71 kDa protein 8 (HSPA8)on the surface of SH-SY5Y cells - Akhter, Shamim; Chakraborty, Sandipan; Moutinho, Daniela; Álvarez-Coiradas, Elia; Rosa, Isaac; Viñuela, Juan; Domínguez, Eduardo; García, Angel; Requena, Jesús R. (PLOS ONE, 2017)
VGF (non-acronymic)is a secreted chromogranin/secretogranin that gives rise to a number of bioactive peptides by a complex proteolysis mechanism. VGF-derived peptides exert an extensive array of biological effects in energy metabolism, mood regulation, pain, gastric secretion function, reproduction and, perhaps, cancer. It is therefore surprising that very little is known about receptors and binding partners of VGF-derived peptides and their downstream molecular mechanisms of action. Here, using affinity chromatography and mass spectrometry-based protein identification, we have identified the heat shock cognate 71 kDa protein A8 (HSPA8)as a binding partner of human TLQP-21 on the surface of human neuroblastomaSH-SY5Y cells. Binding of TLQP-21 to membrane associated HSPA8 in live SH-SY5Y cells was further supported by cross-linking to live cells. Interaction between HSPA8 and TLQP-21 was confirmed in vitro by label-free Dynamic Mass Redistribution (DMR) studies. Furthermore, molecular modeling studies show that TLQP-21 can be docked into the HSPA8 peptide binding pocket. Identification of HSPA8 as a cell surface binding partner of TLQP-21 opens new avenues to explore the molecular mechanisms of its physiological actions, and of pharmacological modulation thereof.